2020
DOI: 10.1093/infdis/jiaa558
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Pneumococcal Carriage in Adults: A New Look at an Old Paradigm

Abstract: Background Limited information is available on pneumococcal colonization among adults. We studied pneumococcal carriage dynamics in healthy adults using high-sensitivity approaches Methods Eighty-seven adults (25-50 years old), were followed for six months in Portugal. Nasopharyngeal, oropharyngeal and saliva samples were obtained monthly; pneumococcal carriers were also sampled weekly. Carriage was investigated by real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 36 publications
5
49
0
Order By: Relevance
“…By revisiting samples negative in primary culture yet positive by qPCR with culture qPCR-guided culturing we have significantly increased the number of adult carriers from whom viable pneumococci were isolated. It demonstrates that molecular methods can improve the overall sensitivity of S. pneumoniae detection, a result in line with previous reports by us and others [7, 16, 18, 22, 46]. It also highlights that the gold standard method applied to oropharyngeal cultures severely underestimates presence of S. pneumoniae in adults as qPCR-guided culturing increased by 7.7-fold the number of oropharyngeal samples from which viable pneumococci were isolated.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…By revisiting samples negative in primary culture yet positive by qPCR with culture qPCR-guided culturing we have significantly increased the number of adult carriers from whom viable pneumococci were isolated. It demonstrates that molecular methods can improve the overall sensitivity of S. pneumoniae detection, a result in line with previous reports by us and others [7, 16, 18, 22, 46]. It also highlights that the gold standard method applied to oropharyngeal cultures severely underestimates presence of S. pneumoniae in adults as qPCR-guided culturing increased by 7.7-fold the number of oropharyngeal samples from which viable pneumococci were isolated.…”
Section: Discussionsupporting
confidence: 88%
“…The addition of the culture-enrichment procedure prior to molecular detection reduces the risk of misclassifying these events as carriage, thus improving the specificity of detection for live pneumococci. Culture-enrichment also increases the sensitivity of carriage surveillance, in particular for poly-microbial samples [7, 18, 2124, 4648]. Indeed, we observed that S. pneumoniae detection in culture-enriched samples displayed significantly increased, sensitivity, specificity, and agreement with culture and qPCR-guided culture when compared with detection in minimally processed samples.…”
Section: Discussionmentioning
confidence: 68%
“…Also, a change in patient characteristics over time could have an impact on the risk of co-infection. Some researchers warned of a potential increase in pneumococcal colonization among adults as a result of close contact with children (Almeida et al, 2021). It would be logical, therefore, to believe that following at-home confinements, contact between adults and children may have been especially close, potentially increasing pneumococcal colonization of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In order to conduct this work, we took advantage of a longitudinal study that our group conducted previously, among adults aged between 25–50 years old. The details of the study design have been described previously [ 21 ]. Briefly, between February 2015 and December 2016, 87 adults aged 25–50 years old, living in the Lisbon area, were followed for 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…Nasopharyngeal samples were collected using a flexible swab with a flocked nylon fiber tip (reference 482CE from Copan) and oropharyngeal samples were collected with a rigid swab with a flocked nylon fiber tip (reference 480CE from Copan) as described previously [ 21 ]. Saliva was collected by spitting into a tube.…”
Section: Methodsmentioning
confidence: 99%